Poor quality of life and incomplete self-reported adherence predict second-line ART virological failure in resource-limited settings. Issue 10 (3rd October 2021) - Torres, Thiago S.; Harrison, Linda J.; La Rosa, Alberto M.; Zheng, Lu; Cardoso, Sandra W.; Ulaya, Godwin; Akoojee, Nazim; Kadam, Dileep; Collier, Ann. C.; Hughes, Michael D.; ,
ABSTRACT: We evaluated health-related quality of life (QoL) and self-reported incomplete adherence as predictors of early second-line antiretroviral (ART) virological failure (VF). ACTG A5273 study participants completed the ACTG SF-21 measure which has 8 QoL domains. We used exact logistic regression to assess the association of QoL at baseline and week 4 with early VF adjusted for self-reported adherence. Of 500 individuals (51% women, median age 39 years) in this analysis, 79% and 75% self-reported complete adherence (no missing doses in the past month) at weeks 4 and 24, respectively. Early VF was experienced by 7% and more common among those who self-reported incomplete adherence. Participants with low week 4 QoL scores had higher rates of early VF than participants with high scores. After adjusting for self-reported adherence at week 4, VL and CD4 at baseline, cognitive functioning, pain and mental health domains were significantly associated with subsequent early VF. In this post-hoc analysis, poorer QoL adds to self-reported incomplete adherence after 4 weeks of second-line ART in predicting VF at week 24. Evaluation is needed to assess whether individuals with poorer QoL might be targeted for greater support to reduce risk of VF. Trial registration: ClinicalTrials.gov identifier: NCT01352715 .